Organic geochemistry and mineralogical characterization of the Paleocene Ranikot Formation shales in selected areas of Southern Indus Basin Pakistan - Hussain Asghar; Saeed Abbas; Muhammad Sabir Khan; Samina Jahandad; Muhammad Hanif; Muhammad Saleem Mughal; Gulfam Hussain (Kuwait Journal of Science)
In this paper we described the geochemical and mineralogical characterization of Ranikot Formation shales in the southern Indus Basin of Pakistan. Southern Indus Basin is one of the promising regions in Pakistan as a commercially producing oil and gas perspective. Therefore, this research focuses on the Ranikot Formation shales from the southern Indus Basin Pakistan. Based on total organic carbon (TOC), Rock-Eval (RE) pyrolysis, organic petrography, gas chromatography-mass spectrometry (GC-MS) and X-ray diffraction (XRD) analyses, the organic geochemical and mineralogical characterization of the Ranikot Formation shales were carried out. The average total organic carbon (TOC) of Ranikot shale is 4.6 wt. % indicating very good source rock.  The RE results imply that the type of kerogen in Ranikot shale are Types III/IV. More clear evidence about kerogen Type came from maceral analyses of the Ranikot shales. The maceral data suggest that Type of kerogen present in Ranikot shale is dominantly Types II-III, with the minor occurrence of Type IV. The vitrinite reﬂectance, pyrolysis Tmax and methylphenanthrene indices values indicate that the Ranikot shales are immature for hydrocarbon generation. The normal alkane data reflect that marine macrophytes, algae and land plants were contributed to the organic matter of Ranikot shales. Dibenzothiophene/phenanthrene ratio 0.11 and phytane/n-C18 ratio 0.53, pyrite and glauconite elucidate that depositional environment of the Ranikot shale is marine.